Expert consensus on BRCA1/2 gene testing and clinical application in Chinese breast cancer patients (2025 edition) - WANG Hongxia, YIN Yongmei, HU Xichun (Zhongguo aizheng zazhi)
Breast cancer remains one of the frequently diagnosed malignant tumors among Chinese women, with hereditary cases accounting for 5%-10% of all diagnoses, where BRCA1/2 gene mutations serve as the primary genetic predisposition factors. Although targeted therapies like poly (ADP-ribose) polymerase (PARP) inhibitors have significantly improved prognoses for patients with BRCA-mutated breast cancer in recent years, critical clinical challenges persist, including the standardization of genetic testing protocols, optimization of precision treatment approaches, and refinement of long-term management strategies. In response to these challenges, our expert panel has conducted a comprehensive update to the 2018 Edition of this consensus by integrating the latest global evidence-based medical research with China’s unique clinical practice characteristics. This 2025 Edition provides systematic evaluations and recommendations on five key aspects: indications for BRCA1/2 gene testing, testing methodologies, result interpretation, treatment strategies, and risk management. The main updates include: ① Increasing the relationship between BRCA1/2 gene mutations and programmed death ligand-1 (PD-L1) expression, as well as related content on BRCAness types; ② Standardizing the application of genetic testing, such as increasing the significance, timing, and sample selection of clinical testing, and optimizing the BRCA testing population; ③ Updating treatment strategies, such as non-drug treatment of BRCA1/2 gene mutation, treatment of triple negative breast cancer (TNBC) patients with BRCA1/2 gene mutation, treatment decisions of hormone receptor (HR)+/human epidermal growth factor receptor 2 (HER2)- breast cancer patients with BRCA1/2 gene mutation, clinical use of PARP inhibitors and adverse reaction management; ④ Addion of relevant content on long-term risk management, such as covering follow-up management, indications for preventive surgery, quality control and requirements for new genetic testing, updating genetic testing processes, report content and interpretation. This consensus aimed to establish standardized diagnostic and therapeutic frameworks for clinicians, advance precision medicine in BRCA-mutated breast cancer, and ultimately improve patient survival outcomes. As new evidence emerges, continuous updates will be implemented to incorporate the latest research findings. This consensus has been registered on the Practice guideline REgistration for transPAREncy (PREPARE) platform (registration number: PREPARE-2025CN1085).